AKTIVITAS HIPOKOLESTEROLIMIK EKSTRAK ROSELA (Hibiscus sabdariffa) PADA TIKUS PUTIH DIABETES - Adhy Nugroho, Christianto (Widya Warta, 2012)
Rosela is one of medicinal herbs. The aim of the study was to find out the hypocholesterolimic effect of oral intake of Rosela extract on diabetic white rat.This research applied Complete Randomized Design of four groups with five replications to each. The treatment for those groups was: no treatment, metformin 9 mg/200 g body weight, 250 mg/kg body weight of Rosela extract, and 500 mg/kg body weight of Rosela extract. The parameters used were cholesterol concentration before and after the treatment.The result showed that the extract of Rosela reduced cholesterol concentration.